Nonsteroidal Anti-Inflammatory Agents in the Treatment of Asthma in Children - Pierre Gaudreault (Canadian Respiratory Journal)
The increasing scientific information clearly demonstrates the important role of inflammation in asthma. This evidence has led physicians to focus their treatment on the elimination of inflammation instead of working solely against bronchoconstriction. Steroids and nonsteroidal agents are currently used to prevent this inflammatory component. This paper focuses only on nonstcroidal anti-inflammatory agents such as sodium cromoglycate, nedocromil sodium and ketotifen and their use in pediatric asthma. The discussion on each medication addresses its mechanism of action, the evidence concerning its efficacy in pediatrics (ie, clinical pharmacology, acute bronchial challenge, late asthmatic response, bronchial hyperrcactivity, clinical efficacy) and the pediatric dose.